Hailstones and their effects on aircraft - SAHA, Sqn. Ldr. K. R. (MAUSAM, 1961)
To explain formation of large hailstones, which cause serious damages to aircraft, current theories regarding the formation and growth of hailstones are reviewed in the light of observed structure of hailstones and physical conditions inside large convective clouds. The role played by updraft is discussed in detail. Following Schumann (1938) an equation is give for the ultimate diameter of a hailstone in terms of updraft velocity, concentration of condensed water at temperatures below 0oC, average density of the hailstone and the depth of fall above the freezing level. Substitution of mean as well as extreme values of the different parameters involved in the equation seem to show that hailstones of sizes 10-12 cm in diameter would not be infrequent in the tropics although an extreme size of 18 cm in diameter would certainly be a rare occurrence. Observed damages to aircraft by hailstones suggest impact at low angles of elevation and this is explained by a consideration of relative fall velocity (terminal velocity-updraft velocity) and the speed of aircraft. The meteorological problem of forecasting hailstorms is discussed and it is concluded that in the present state of our knowledge safety considerations would demand a more reliable guide to aviators, viz., an airborne radar which can provide early warning of severe hailstorm cells while in flight.